Molecular characterization of clinical carbapenem-resistant Enterobacterales from Qatar - Fatma Ben Abid; Clement K. M. Tsui; Yohei Doi; Anand Deshmukh; Christi L. McElheny; William C. Bachman; Erin L. Fowler; Ahmed Albishawi; Kamran Mushtaq; Emad B. Ibrahim; Sanjay H. Doiphode; Manal M. Hamed; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
One hundred forty-nine carbapenem-resistant Enterobacterales from clinical samples obtained between April 2014 and November 2017 were subjected to whole genome sequencing and multi-locus sequence typing. Klebsiella pneumoniae (81, 54.4%) and Escherichia coli (38, 25.5%) were the most common species. Genes encoding metallo-β-lactamases were detected in 68 (45.8%) isolates, and OXA-48-like enzymes in 60 (40.3%). bla NDM-1 (45; 30.2%) and bla OXA-48 (29; 19.5%) were the most frequent. KPC-encoding genes were identified in 5 (3.6%) isolates. Most common sequence types were E. coli ST410 (8; 21.1%) and ST38 (7; 18.4%), and K. pneumoniae ST147 (13; 16%) and ST231 (7; 8.6%).